The Impact of Social Class and Ability Group on Students Academic Achievement: a Case Study of Selected Primary Schools - Salmah, Siti; Nisak, Khoirun; Syafiani, Angela; Bulan, Linda Sari (Universitas Muhammadiyah Mataram, 2022)
Ability group system (AGS) can be understood as grouping students according to their academic abilities. There are pros and cons of the ability group implementation in schools. However, this system is still practised in modern national educational systems. The present study explored the impact of students’ socioeconomic status (SES) and the AGS implementation on selected primary students’ academic achievement. The research utilised the qualitative method and followed a case study design confined to a selected primary school that implemented the ability group system in their teaching and learning process. A total of 12 informants were selected using the purposive sampling technique. The sample consisted of four teachers with experience adopting ability groups in the teaching and learning process and eight parents who have children in different ability level classes. Data was obtained using semi-structured interviews, non-participant classroom observation, and document analysis. The findings demonstrate that SES background and AGS could impact students’ academic performance. Therefore, this study suggested that the improving of group ability implementation in schools is crucial, such as teaching method and strategies that teacher use in different level of group ability should be improved. Also schools should provide a sufficient training for teacher to implement group ability system.